Legal Updates 2025 (Ibrachy & Dermarkar law Firm, 2025)
OFFICIAL JOURNAL – ISSUE 6 (BIS - B) - DATED 9 FEBRUARY, 2025 LAW NO. 2 OF THE YEAR 2025 AMENDING CERTAIN PROVISIONS OF LAW NO. 232 OF THE YEAR 1989 ON SHIPS SAFETY